2019
DOI: 10.1002/jcp.28995
|View full text |Cite
|
Sign up to set email alerts
|

miR‐182‐5p contributes to intestinal injury in a murine model of Staphylococcus aureus pneumonia‐induced sepsis via targeting surfactant protein D

Abstract: Sepsis is a severe clinical disease, which is resulted from the excessive host inflammation response to the infection. Growing evidence indicates that Staphylococcus aureus pneumonia is a significant cause of sepsis, which can lead to intestinal injury, inflammation, and apoptosis. Studies have shown that miR-182-5p can serve as a tumor oncogene or a tumor suppressive microRNA in various cancers, however, its biological role in sepsis is still uninvestigated. Here, we reported that miR-182-5p was obviously inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…Moreover, SP-D was reduced significantly in pneumonia mice models. It binds with the bacterial pathogens and eradicate the pathogens and apoptotic bodies, playing vital role in the regulation of immune responses (Du et al, 2019). In another study, it was demonstrated that SP-A and SP-D diminished severity of S. aureus pneumonia and gut mucosal injury.…”
Section: Staphylococcus Aureus Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SP-D was reduced significantly in pneumonia mice models. It binds with the bacterial pathogens and eradicate the pathogens and apoptotic bodies, playing vital role in the regulation of immune responses (Du et al, 2019). In another study, it was demonstrated that SP-A and SP-D diminished severity of S. aureus pneumonia and gut mucosal injury.…”
Section: Staphylococcus Aureus Pneumoniamentioning
confidence: 99%
“…The mechanisms by which the gut microbiota influences on the immune responses and inflammation in the lungs, and vice versa, are being extensively studied. The involvement of regulatory T cell subsets (Ohnmacht, 2016;Lee and Kim, 2017;Luu et al, 2017) and Toll-like receptors (TLRs) (O'Dwyer et al, 2016;Wang et al, 2018), inflammation cytokines and mediators (Scales et al, 2016), surfactant protein D (Du et al, 2019) and several other factors have been proposed as the underlying mechanisms, but many details unknown. Nevertheless, novel therapeutic strategies that target manipulation of gut microbiome by anti-biotics, probiotics, prebiotics, natural products, or diets have been attempted in various lung diseases by clinical and laboratory studies.…”
Section: Introductionmentioning
confidence: 99%
“…SP-D can repress the pneumonia severity and the intestinal injury of sepsis in rats [30]. Previously, we reported that miR-182-5p induces intestinal injury in a murine model of sepsis via targeting SP-D [31]. Currently, we found that SP-D was decreased in sepsis mice.…”
Section: Discussionmentioning
confidence: 89%
“…[ 38 ] miR‐182‐5p targets surfactant protein D to facilitate intestinal injury in sepsis induced by Staphylococcus aureus pneumonia. [ 39 ] miR‐182‐5p regulates Cofilin 1 to affect cell proliferation, migration, and invasion in human bladder cancer. [ 40 ] However, the relationship between CHRF and miR‐182‐5p in myocardial I/R injury is not clear.…”
Section: Discussionmentioning
confidence: 99%